The Role of Customer Satisfaction in Moderating the Effect of Brand Image and Service Quality on Loyalty - Razzak, Hasbi; Zaerofi, Afif (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study examines the factors that influence customer loyalty at Islamic banks in West Java in the face of increasingly fierce competition in the Islamic banking industry. The research focuses on brand image, service quality, and customer satisfaction, highlighting the moderating role of customer satisfaction. The uniqueness of this study lies in the in-depth exploration of how customer satisfaction serves as a moderator that strengthens the relationship between brand image and loyalty in the religious preferences of the people of West Java. Data was collected from Islamic bank customers in West Java using purposive sampling method, with a total of 259 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software version 24. The results showed that brand image, service quality, and customer satisfaction have a positive and significant effect on loyalty. In addition, customer satisfaction moderates the relationship between brand image and loyalty, strengthening customer trust and long-term commitment. This research introduces a new perspective by integrating the religiosity dimension as an intrinsic factor that influences the effectiveness of Islamic banks' strategies in increasing customer loyalty. The practical implication is that Islamic banks should enhance customer experience through specific strategies, such as providing intensive training to improve employees' service skills, using technology to ensure service efficiency and convenience, and developing marketing campaigns that are consistent with Islamic values. In addition, proactive and transparent complaint management can strengthen customer relationships. These measures are important to strengthen brand image, improve service quality, and foster loyalty in the long run.